2011
DOI: 10.1007/s11094-011-0631-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antibacterial, and antifungal activities of 8-quinolinealdehyde chalcogensemicarbazones and their copper(II) complexes

Abstract: The antibacterial and antifungal activities of a series of 8-quinolinealdehyde chalcogensemicarbazones have been studied. Only the selenium analog shows activity against Gram-positive bacteria. 8-Quinolinealdehyde thiosemicarbazone becomes active against the indicated bacteria upon coordination to copper(II) ions. The antibacterial activity of the obtained complexes depends on neither the nature of the anion nor the form (molecular or anionic) of the ligand. Introduction of electron-accepting groups on the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A few comprehensive comparative studies of (chalcogen)semicarbazones and their complexes pointed out the importance of the chalcogen donor atom identity for biological activity. 26,30,38 Among the three types of (chalcogen) semicarbazones, thiosemicarbazones have been studied to a greater extent than semicarbazones and selenosemicarbazones. Some results indicated that sulphur compounds are more active in comparison with oxygen analogues, which showed a rather limited spectrum of biological activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few comprehensive comparative studies of (chalcogen)semicarbazones and their complexes pointed out the importance of the chalcogen donor atom identity for biological activity. 26,30,38 Among the three types of (chalcogen) semicarbazones, thiosemicarbazones have been studied to a greater extent than semicarbazones and selenosemicarbazones. Some results indicated that sulphur compounds are more active in comparison with oxygen analogues, which showed a rather limited spectrum of biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…37,39,40 Selenosemicarbazones and their metal complexes have been an area of our particular interest for years. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]41,42 Research suggests that the mechanisms of cytotoxicity of these compounds may include the production of reactive oxygen species and oxidative stress in the complexes with 2-quinolinecarboxaldehyde selenosemicarbazone. 37 In the current study we used 8-quinolinecarboxaldehydebased (chalcogen)semicarbazones as ligands (Scheme 1), providing detailed spectroscopic and structural characterization (X-ray diffraction, XRD) of the novel cobalt complexes with oxygen and sulphur-based ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain more active species, complexes of Pt(II), Pd(II), Zn(II), Cd(II), Au(I), Ni(II), Co(III), Ga(III), Sn(IV) and Cu(II) have been prepared and tested against malaria, 10, 24, 25 microorganisms, [3][4][5] as well as cancer cell lines. 3,11,[16][17][18][19][20][21][22][23]26 As a result of such approach metal complexes with activities better than corresponding ligands have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Copper is one of the 26 essential nutrients in human, participating in the metabolic activities [21]. Additionally, copper has been widely reported for its broad antibacterial properties [22][23][24][25]. In 2008, copper was the first metal to receive EPA certification [26].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%